Characterization of Livelihood Systems in Coral Ecosystem - Beevi, Anshida; Wason, Monika (Indian Journal of Extension Education, 2015)
A livelihood comprises the capabilities, assets and activities required for a means of living. The present study has  undertaken to characterize the livelihood systems in coral islands of India. Out of 11 inhabiting islands of Lakshadweep,  two islands “Kalpeni” and “Andrott” were selected for the study. From the islands selected, two wards and from each  ward 30 individuals were selected by simple random sampling technique. A total of 120 respondents comprised the  sample. The results showed that three livelihood groups in the study area include the farming alone (group 1), non-farm  activities alone (group 2) and both farm and non- farm activities (group 3). Activity ranking exercise was done based on  different activities carried out by the islanders for means of living. It shows that group 3 is engaged in more diversified  activities as their livelihood source.
Keywords: Characterization; livelihood system